The Federal Democratic Republic of Ethiopia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper assesses the implications of a significant increase in the flow of external financing and grants on real GDP growth in Ethiopia. The paper presents an analysis of the sources of growth during 1991/92-2003/04, as well as an assessment of potential GDP growth. The paper also seeks to assess the historical relationship between foreign aid and the performance of the external sector in Ethiopia to establish whether foreign aid inflows have had an adverse effect on the tradable goods sector in the past.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet